Analisis Kinerja Keuangan Dengan Menggunakan Metode CAMEL Pada PT. Bank Rakyat Indonesia (persero) Tbk - Fransiskus Freklindo; Yosefina Andia Dekratia; Magdalena Samosir (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
This study aimed to determine the financial performance of PT. Bank Rakyat Indonesia (Persero) Tbk using the CAMEL method, namely Capital, Asset, Management, Earning, Liquidity. The sample in this study was the financial statements of BRI companies in 2018-2022. The type of data used was secondary data. Data collection was carried out using the documentation method, the data source was taken from the official website of the Indonesia Stock Exchange. The results showed that the performance of PT. BRI for the period 2018-2022 using the CAMEL method was in a healthy predicate. While from each aspect, namely the aspects of Capital(Capital), Asset aspects (Asset Quality), and Earning (Income) for 5 years are in a healthy manner. Meanwhile, the Management aspect for 4 years, namely 2018, 2019, 2020, and 2022, was in a fairly healthy predicate, while in 2021 it was in a healthy predicate. Liquidity in 2018 and 2019 was in a fairly healthy predicate, while from 2020 to 2022 obtained a healthy predicate.